7-digit Product-level Supply-Use and Input-Output Tables Using ASI Data - Sourish Dutta (Cambridge University Press, Cambridge Open Engage, 2025)
This paper constructs 7-digit product Supply-Use Tables (SUTs) and symmetric Input-Output Tables (IOTs) for the Indian economy using microdata from the Annual Survey of Industries (ASI) for the period 2016-2021. We outline the methodology for generating input flows and reconciling registered and unregistered sector data via NPCMS-NIC concordance. The transition from SUTs to IOTs is explained using the Industry Technology Assumption. We apply this framework to analyse the economic impact—specifically Domestic Value Added (DVA) and employment influenced by production and exports. A case study of India's mobile phone sector reveals significant output growth, import substitution, an increase in exports, a shift in DVA/FVA shares, notable employment growth, with a leaning towards contractual labour, and increased female participation. These tables are valuable for analysing sectoral interdependencies and industrial policy effectiveness in India.
Conference: 43rd Annual Conference of the Indian Association for Research in National Income and Wealth (IARNIW), National Statistical Office (NSO) in the Institute of Economic Growth (IEG), New Delhi; Additional information: A summarised version is published in Economic Survey 2023-24 (Ch. 10, p. 360).
Keywords: 330; Supply-Use Tables (SUTs); Input-Output Tables (IOTs); Annual Survey of Industries (ASI); Manufacturing Sector; Domestic Value Added (DVA); Employment Linkages; Backward Linkages; Mobile Phone Industry; NPCMS; KLEMS; Industry Technology Assumption; India